2014
DOI: 10.1186/2050-6511-15-18
|View full text |Cite
|
Sign up to set email alerts
|

The development of response surface pathway design to reduce animal numbers in toxicity studies

Abstract: BackgroundThis study describes the development of Response Surface Pathway (RSP) design, assesses its performance and effectiveness in estimating LD50, and compares RSP with Up and Down Procedures (UDPs) and Random Walk (RW) design.MethodsA basic 4-level RSP design was used on 36 male ICR mice given intraperitoneal doses of Yessotoxin. Simulations were performed to optimise the design. A k-adjustment factor was introduced to ensure coverage of the dose window and calculate the dose steps. Instead of using equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 20 publications
(26 reference statements)
0
40
0
Order By: Relevance
“…Development of the concept in laboratory animals and computer simulations demonstrated that this is not an optimal solution. 11 Starting with a low number of subjects and increasing this number with succeeding design levels reduces the sample size without reducing the accuracy of the estimates. This procedure is not possible in the within-patient situation, but can be implemented in the …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Development of the concept in laboratory animals and computer simulations demonstrated that this is not an optimal solution. 11 Starting with a low number of subjects and increasing this number with succeeding design levels reduces the sample size without reducing the accuracy of the estimates. This procedure is not possible in the within-patient situation, but can be implemented in the …”
Section: Discussionmentioning
confidence: 99%
“…11 By starting with a low number of patients at the first design level and increasing this number with increased level, the sample size reduces without reduction in accuracy. This is possible in the between-patient RSP design using randomization.…”
Section: Rsp Designmentioning
confidence: 99%
See 3 more Smart Citations